Seed Conservation of Anaxagorea luzonensis A. Gray (Annonaceae) Through Storage Behaviour and Morphology - Lestari, Dewi Ayu; Faya, Ananda Kautsar Nadia (Universitas Gadjah Mada, 2024)
Fruits and seeds morphological traits and seed storage behaviour of Anaxagorea luzonensis are important for seed and plant conservation. Fruits and seeds characterization using a digital microscope and morphometry method. Seed storage behaviour was determined using 100-seed test method. The findings revealed that the colour of A. luzonensis fruit did not change and A. luzonensis seed was glossy, brittle, black in colour, 9.05 x 5.89 x 2.93 mm sized and oval. The seeds are desiccation-tolerant and are categorized as orthodox seeds. These results can become the findings of A. luzonensis seed storage behaviour, because information about it never existed before. Knowing the seed storage behaviour and seed morphology of A. luzonensis is essential so that the recommendation of conservation efforts at PBG in the future are covering the fruit, modifying the environment, breaking dormant seeds, vegetative propagation, and preserving seeds.